All Cognitive Systems but Speed and Visuospatial Functions Reduce the Effect of CSF Pathology on Other Systems - Rolstad, Sindre; I. Berg, Anne; Zetterberg, Henrik; Johansson, Boo; Wallin, Anders (Current Alzheimer Research, 2012)
The concept of reserve can be conceived as differences in the ability to compensate for pathology by recruiting additional or alternative networks. The purpose of this study was to examine whether certain cognitive systems may compensate for the effect of CSF amyloid beta 42 (Aβ42) and total tau (T-tau) on other cognitive systems. Five hundred and nine participants underwent neuropsychological examination and lumbar puncture. Multiple regression was performed with interaction terms to test whether a cognitive system reduced the impact of CSF pathology on other systems. All cognitive systems except speed and visuospatial functions were associated with reduced effects of T-tau and Aβ42 on semantic memory, working memory and visuospatial abilities. The burden of Aβ42 was reduced more often than that of T-tau. Our results suggest that most cognitive systems may be beneficial to maintenance of cognitive performance despite CSF burden. The results support the notion of cognitive reserve.
Keywords: Cerebrospinal fluid